Performance Monitoring, Subordinate’s Felt Trust and Ambidextrous Behavior; Toward a Conceptual Research Framework - Ahmed, Farooque; Soomro, Shuaib Ahmed; Tunio, Fayaz Hussai; Ding, Yi; Qureshi, Naveed Akhtar (Frontiers in Psychology, 2022)
The present research proposes an electronic performance monitoring framework based on ambidextrous leadership and social exchange theories in a dynamic environment. It reviews and integrates essential literature on electronic performance management (EPM), trust, and ambidextrous behavior. For this, authors have reviewed relevant literature on various themes and underpinned them for managing EPM. The study emphasizes individuals’ psychological foundations that demonstrate trust behavior and relationship with their leaders. Eventually, through an ambidextrous approach, managers gain steady performance and relationships with their subordinates through EPM. The study shows that ambidexterity benefits organizations; it enhances employees’ resources, resulting in enhanced performance that leads to the performance of an organization. The authors discuss the theoretical as well as practical implications of this study.